Why do differences in the degree of fiscal decentralization endure? - Xavier Calsamiglia; Teresa Garcia-Milà; Therese J. McGuire (Center for Economic Studies and ifo Institute (CESifo), 2006)
Differences in the degree of fiscal decentralization observed between the U.S. and many countries in Europe cannot be explained within the standard theory of fiscal decentralization. By introducing preferences for solidarity - equality in the provision of public goods and services across regions - we show that different decentralization schemes can coexist as efficient choices. We develop a model of fiscal decentralization that incorporates tastes for solidarity, multiple levels of government, and various tax and transfer instruments. We find that when solidarity is added to the traditional fiscal-federalism framework, the choice along the decentralized-to-centralized spectrum shifts toward a more centralized system.
Keywords: H2; H4; H7; 330